Guo Moruo on Marx and Confucius - Bart DESSEIN (Asian Studies, 2019)
Through the analysis of two of Guo Moruo’s literary works––his “Marx Enters a Confucian Temple” published in 1926, and “Confucius Eats” published in 1935––Guo Moruo’s assessment of Confucius and Marx is discussed. It is shown how Guo Moruo, although being a self-declared Marxist, kept on adhering to some Confucian principles, and how this attitude of his helps to explain why Guo Moruo, after having been criticized in the “pi Kong pi Lin” campaign, is now, within the revival of Confucianism in the People’s Republic of China, being revaluated.